Evaluation of lipid metabolism in the rumen - Dock, Lauren (Kansas State University, 2022)
Lipids as nutrient sources have been researched for many years. Dietary lipids can increase the efficiency of ruminant production and create a better quality of meat that has positive human health benefits. Lipid inclusion in rations increases dietary energy content. This review discusses biohydrogenation as a major pathway for lipids. Whereas unsaturated fatty acids are good for cattle, they are more toxic than saturated fatty acids to the bacteria in the rumen, and longer chain fatty acids have a higher toxicity; therefore biohydrogenation must take place (Lock et al., 2006). The process of biohydrogenation of fatty acids is to reduce the unsaturated fatty acids into saturated fatty acids using hydrogenation (Byers and Schelling, 1988). Biohydrogenation, which usually is greater than 80% of dietary unsaturated fatty acids, occurs in relation to fine food or feed particles, which allows for extracellular enzymes of bacteria to either associate with the feed or be free within the rumen (Harfoot and Hazlewood, 1997). The first step of biohydrogenation is isomerization to convert the cis configuration to the trans configuration. Conjugated linoleic acids are isomers of linoleic acid with conjugated double bonds separated by one single carbon-carbon bond, and the double bonds can be of cis or trans configurations (Lehnen et al., 2015). In dairy cattle, dietary lipids can improve efficiency of energy utilization for milk production, and in feedlot cattle dietary lipids can improve feed efficiency. This review of lipids in ruminants provides insight into how digestion, fatty acid metabolism, and microbial activity are affected when lipids are added to the diet.
Keywords: Biohydrogenation; Fermentation; Benefits; Ruminant